PENGUATAN PENDIDIKAN KARAKTER PEDULI LINGKUNGAN - Meiman Waruwu; Seberman Lawolo; Yolan Ardian Zebua; Juni Mustahil Gea; David Ronaldo Zai; Opi Rahmat Damai Hulu; Wiranti Amazihono (LPPM Institut Pendidikan Nusantara Global, 2025)
Increasingly complex environmental issues require the active involvement of the younger generation, particularly students, in building awareness and responsibility for ecological sustainability. This community service activity aims to instill and strengthen environmental values among students of the Faculty of Economics through an educational-participatory approach. The implementation method consists of three stages: preparation (coordination and understanding mapping), implementation (seminars and interactive discussions), and evaluation (pre-test and post-test). The results of the activity showed a significant increase in students' knowledge, attitudes, and action plans regarding environmental issues. Students not only understood the importance of environmental character but also began to show initiative in getting involved in environmental movements on and off campus. This activity proves that environmental-based character education can be an effective strategy in developing empowered and ecologically aware agents of change among economics students.